Study On Improvement Water Deposition on Vehicle Side Mirror - Amirul Syahmi Bin Azhar; Rahmah Binti Mahmudin (Progress in Engineering Application and Technology, 2023)
Outside rear view mirrors contribute to enable the driver to see the back of the car when parking or driving down the road. The air turbulence caused by passing through the side mirror’s neck will cause a raindrop to cover the car’s front door windows. Additionally, Malaysia has a tropical climate, which means that it frequently has rainy days. This situation will result in water deposition near door windows mirror, especially in the front area. The objective of this study is to minimizing water deposition on the outside rear view mirror. Additionally, one of the major goals of this study is to evaluate the model’s simulation using ANSYS software. To prepare for this research, a model must been scan by 3D scanner, with the shark fin features will add using the SolidWorks software, and the simulation ran using the ANSYS software. To execute a test with specific conditions for the new model, the boundary condition will be specified towards it in the ANSYS software. Based on finding that been get, the model without any additional shark fin has a better result of turbulence kinetic energy but has worst result on outside rear view mirror. For the model with additional shark fin has a little bit improvement at outside rear view mirror. Therefore, it can be concluded that the addition of a shark fin, particularly at the base of the outside rear view mirror, can contribute to the reduction of turbulence kinetic energy and improve aerodynamic performance in terms of water deposition. To enhance the quality of data in future research, several recommendations can be proposed. Firstly, during the meshing process in the ANSYS simulation, it is advisable to employ a more detailed meshing technique.